Breast reconstruction: 10 years experience - Izadora Lorena Ferreira Reis; Romeu Ferreira Daroda; Carlaile Soares Franco; Gabriel Felipe Silva; Larissa Silva Leitão Daroda (Revista Brasileira de Cirurgia Plástica)
Introduction: Breast reconstruction after surgical treatment for breast cancer (one of the main cancers that affect women) has been progressively more recommended, given the benefits of psychological recovery and quality of life, whether using implants and/or autologous tissues. The present work aims to demonstrate the team’s experience, and discuss operative techniques and complications concerning data from the world literature, in addition to verifying the applicability of the technique in the team’s clinical practice. Method: Retrospective observational study developed at a university hospital in Juiz de Fora based on a review of medical records of patients who underwent mastectomy with breast reconstruction between 2010 and 2020. Results: Of the 860 breasts treated, 84% underwent immediate oncological surgery and 16% were late; the main access to the breast tissue was the Stewart incision, followed by extended inframammary, periareolar, and inverted T incisions; regarding reconstructive techniques, 35% of cases used a latissimus dorsi muscle flap, 25% used a prepectoral prosthesis, 20% used a transverse rectus abdominis myocutaneous flap and 10% used a local muscle flap. The most common complications were surgical site dehiscence, followed by skin necrosis, seroma, surgical site infection, and hematoma, in addition to other less common complications such as chronic pain and prosthesis rupture after mammography. Conclusion: Post-mastectomy breast reconstruction is essential for a woman’s physical and emotional recovery, with the techniques used in the last ten years being consistent, reliable, with low morbidity, and with excellent aesthetic results when correctly indicated.